You may ask yourself : - Conley, Dalton (w.w.Norton&Company,Inc, 2015)
The “untextbook” that teaches students to think like a sociologist.You May Ask Yourself gives instructors an alternative to the typical textbook by emphasizing the “big ideas” of the discipline, and encouraging students to ask meaningful questions. Conley employs a “non-textbook” strategy of explaining complex concepts through personal examples and storytelling, and integrates coverage of social inequality throughout the text.